2008
DOI: 10.12968/ijpn.2008.14.8.30771
|View full text |Cite
|
Sign up to set email alerts
|

Active carers: living with chronic obstructive pulmonary disease

Abstract: It has long been recognised that the majority of care provided in chronic illness comes not from health and social care professionals, but from family and friends. One such illness is chronic obstructive pulmonary disease (COPD), a leading cause of morbidity and mortality in the developed world.To explore the specific care needs of informal caregivers of patients with advanced COPD, interviews were conducted with seven active family caregivers. Interviews were taped, transcribed and content analysed to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 19 publications
2
113
0
5
Order By: Relevance
“…KOAH'lı hastalarla yaşayan ya da onların bakım sorumluluğunu üstlenen bireyler ciddi fiziksel ve duygusal sorunlar yaşamaktadır [20,21]. Pinto ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…KOAH'lı hastalarla yaşayan ya da onların bakım sorumluluğunu üstlenen bireyler ciddi fiziksel ve duygusal sorunlar yaşamaktadır [20,21]. Pinto ve ark.…”
Section: Discussionunclassified
“…Bu sonucun çalışmaya katılan bireylerin yarıdan fazlasının (%64.2) geniş ailede yaşıyor olması ve kültürel değerlerimizin bir yansıması olarak genellikle kadınların bakım veren olarak algılanmasıyla ilişkili olduğu düşünülebilir. Bakım vericilerin yaş ortalamalarının hastalardan çok daha genç olduğu ve büyük çoğunluğu-nun kadınlardan oluştuğu belirtilmektedir [6,20,21]. Çalışmada yaş ortalaması genç olan bakım vericilerin bakım sorumluluğunu başka biriyle paylaşma oranlarının düşük ve günlük bakım verme sürelerinin ağırlıklı olarak altı saatten uzun olması sonucunun da KOAH'lı bireylerin yaş ortalamalarının (64.43±9.09) yüksek olmasının ve bakım vericilerin hastaların kız çocukları ile gelinlerinden oluşmasının doğal bir sonucu olarak yorumlanabilir.…”
Section: Discussionunclassified
“…Informal caregivers are of major importance for patients with COPD, as the majority of home care is provided by family and friends instead of healthcare professionals [10]. To date, more than 70% of the COPD patients referred for pulmonary rehabilitation have one or more informal caregivers.…”
Section: Role Of Informal Caregiversmentioning
confidence: 99%
“…So, a decrease in hospitalisations can save healthcare costs. Informal caregivers may improve patient adherence [13] and they provide (informal) care at home [10]. Therefore, informal caregiving reduces costs for professional care at home.…”
Section: Role Of Informal Caregiversmentioning
confidence: 99%
“…The latter identifies carers' anxiety/emotional distress 5,[8][9][10][11][12] , isolation 5,13 , restrictions ,5,8,9,11-14 , lack of support/assistance 5,12,14 , lack of knowledge/strategies, helplessness and powerlessness. 5,12,13 However, the evidence-base for interventions to meet these needs remains limited [15][16][17][18] . Bee et al's systematic review of carers' needs in providing home-based end-of-life care to people with cancer suggests that home-based palliative care services have insufficiently focussed on assisting carers to acquire information and practical skills 19 , whilst Caress et al's review found no studies describing or evaluating interventions to enhance caregiving-capacity for family-carers of COPD patients 20 .…”
Section: Introductionmentioning
confidence: 99%